Sexual size dimorphism in selected traits of Leptodactylus luctator (Anura: Leptodactylidae) - Salguero, Jerónimo (2024)
Fil: Salguero, Jerónimo. Universidad Nacional de Córdoba, Argentina. Facultad de Ciencias Exactas, Físicas y Naturales; Argentina.